Assessment of Medical Professionalism in House Officers using Professionalism Assessment Tool (PAT) - Fatemah, Minhal; Zaidi, Narjis; Amjad, Bareera; Nadeem, Misbah; Farheen, Mamoona; Noreen, Khola (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Background: Professionalism is influenced by cultural, religious, and social differences. It must be assessed according to one’s setup. To the best of our knowledge, no method of assessing professionalism specific to Pakistan currently exists. Despite its importance in the healthcare setup of Pakistan, researches assessing medical professionalism in Pakistan are limited. Objectives: The objectives of this study are to determine the reliability of the Professionalism Assessment Tool (PAT) in house officers and to assess the status of medical professionalism among house officers . Materials and Method: A cross-sectional study was conducted among House officers working in the allied hospitals of Rawalpindi Medical University from June 2022 to October 2022. After obtaining written informed consent, each participant was evaluated using the Professionalism Assessment Tool. Data was entered and analysed using SPSS version 25. Results: Total of 300 house officers were included in our study, out of which 62.7%of participants were females and more than half (51.7%) belonged to 25-27 years of age. Reliability was assessed by calculating Cronbach’s Alpha. Results depicted that all subscales reached reliability score of 0.7, with Cronbach’s Alpha value of overall PAT being 0.941, depicting excellent reliability. 45.7% had satisfactory professional behaviour (PAT Score= 48-71); 48.7% scored above 72, indicating good professional behaviour. Conclusion: The study found the Professionalism Assessment Tool (PAT) to be a reliable construct for assessing medical professionalism. Further studies can be conducted to track the professionalism of medical students, postgraduate residents and doctors .